“However, we argue that ...”: The Construction of Authorial Identities in English Research Articles - Hardjanto, Tofan Dwi (Academy Publication, 2022)
s—This research investigates how professional authors construct their authorial identities in English research articles (RAs). Sixty research articles were selected from three disciplines, biology, linguistics, and medicine, published by native and non-native authors in reputable international journals. First-person references in the articles were analyzed qualitatively and quantitatively with the help of corpus linguistic methods to examine the identities they were used to express, their density, and their cross-cultural and cross-disciplinary variation. The findings showed that native and non-native authors frequently employed authorial references in their English RAs. The results showed striking similarities in the density of authorial references and the identities they express in the RAs published by both groups. However, there was a significant difference in authorial references and identities by these groups of authors across different disciplines, with the hard sciences employing significantly more frequent authorial references than the soft sciences. The findings suggest that while research publication at the highest level does not seem to affect the construction of authorial identities, disciplinary practices significantly affect authorial identity construction. It is argued that authorial references may be an essential feature of written academic interaction at the highest level. They allow authors to create identities serving as humble servants to seek cooperation and emphasize solidarity with their disciplinary communities and as knowledge originators to stress personal contribution to their respective disciplines.